Models of Innovation Infrastructure in the Euroregions - Tsekhanovych, V. (Економічний вісник Донбасу, 2019)
The main purpose of the article is to define models of innovative structures in Euroregions. It is on the modern stage of Development of Euroregional cooperation in the innovative sphere and its efficiency is determined by the capacities of a particular region based on the selected models of innovation development, which is influenced by a number of factors: the level of socio-economic development of the region, the state of development of innovation infrastructure, personnel potential in the sphere of innovation, the availability of financial resources for production and innovation, innovation policy, local authorities, the degree of state influence on the innovation processes in the region. The interrelation of these factors determines the opportunities for the development of Euro-regional cooperation in the field of innovation, as well as ways to overcome the problems that stand in the way of activating the innovation activity of the regions of Ukraine. The article also discusses innovative infrastructure of Euroregions, which leads to competitive advantages of the region and the creation of various business entities in the Euroregion. Головною метою статті є визначення моделей інноваційних структур в єврорегіонах. Саме на сучасному етапі розвиток єврорегіонального співробітництва в інноваційній сфері та його ефективність визначається можливостями конкретного регіону з урахуванням вибраної моделі інноваційного розвитку, яка формується під впливом ряду факторів: рівень соціально-економічного розвитку регіону, стан розвитку інноваційної інфраструктури, кадровий потенціал в інноваційній сфері, наявність фінансових ресурсів для виробництва та впровадження інновацій, інноваційна політика місцевих органів влади, ступінь державного впливу на інноваційні процеси у регіоні. Взаємозв'язок цих факторів визначає можливості для розвитку єврорегіонального співробітництва у сфері інновацій, а також шляхи подолання перешкод активізації інноваційної діяльності регіонів України. Також у статті розглядаються інноваційні інфраструктури єврорегіонів, що веде до конкурентних переваг регіону і створення різних бізнес-утворень в єврорегіоні. Главной целью статьи является определение моделей инновационных структур в еврорегионах. Именно на современном этапе развитие еврорегионального сотрудничества в инновационной сфере и его эффективность определяется возможностями конкретного региона с учетом выбранной модели инновационного развития, которая формируется под влиянием ряда факторов: уровень социально-экономического развития региона, состояние развития инновационной инфраструктуры, кадровый потенциал в инновационной сфере, наличие финансовых ресурсов для производства и внедрения инноваций, инновационная политика местных органов власти, степень государственного влияния на инновационные процессы в регионе. Взаимосвязь этих факторов определяет возможности для развития еврорегионального сотрудничества в сфере инноваций, а также пути преодоления препятствий активизации инновационной деятельности регионов Украины. Также в статье рассматриваются инновационные инфраструктуры еврорегионов, что ведет к конкурентным преимуществам региона и созданию различных бизнес образований в еврорегионе.